Adaptive Fuzzy Filter Technique for Mixed Noise Removing from Sonar Images Underwater - Aessa, Suad Ali; Ali, Ekbal Hussain; Shneen, Salam Waley; Abood, Layla H. (Peneliti Teknologi Teknik Indonesia, 2024)
Underwater Analysis of acquired images may be affected by low contrast, haze, and other disturbances., caused by scattering and absorption of the light through propagation. An adaptive fuzzy filter for three mixed noise reduction is adopted on underwater sonar images to take out the various noises that either appear in the image when captured or injected into the image when transmitted. Underwater images when captured usually have speckle noise, salt, pepper noise also Gaussian noise. Is suggested in this paper an adaptive fuzzy filter structure that combines the fuzzy filter, sigmoid sliding control to minimize error as possible, and mean filter to reduce three mixed noises from sonar images underwater. This technique gives the best results especially with speckle noise compared to mean filter, median filter as no adaptive filters, and fuzzy filters, frost filter as adaptive filters. The MATLAB programs are adopted to simulate the proposed system.